The post-thrombotic syndrome - Rabe, E.; Pannier, F. (Phlebologie, 2016)
Post-thrombotic syndrome (PTS) is a common complication of deep vein thrombosis (DVT) in the legs. Risk factors include recurrent ipsilateral DVT, proximal vein involvement, persistent occlusion of the deep venous system, obesity, and pre-existing chronic venous disease. Compression therapy, exercise, and weight loss, as well as effective anticoagulation of the initial DVT and secondary thromboprophylaxis, are all important aspects in the prevention and treatment of post-thrombotic syndrome.
Keywords: Post-thrombotic syndrome; deep vein thrombosis of the legs; compression therapy; risk factors; prophylaxis